2013
DOI: 10.1158/1535-7163.mct-12-0719
|View full text |Cite
|
Sign up to set email alerts
|

Selective Disruption of Rb–Raf-1 Kinase Interaction Inhibits Pancreatic Adenocarcinoma Growth Irrespective of Gemcitabine Sensitivity

Abstract: Inactivation of the Retinoblastoma tumor suppressor protein, (Rb), is widespread in human cancers. Inactivation of Rb is thought to be initiated by association with Raf-1 (C-Raf) kinase, and here we determined how RRD-251, a disruptor of the Rb-Raf-1 interaction, affects pancreatic tumor progression. Assessment of phospho-Rb levels in resected human pancreatic tumor specimens by immunohistochemistry (n=95) showed that increased Rb phosphorylation correlated with increasing grade of resected human pancreatic ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Our observations are consistent with other studies, which have found that high expression of phospho-RB1 is associated with an increasing degree of tumor aggressiveness in a variety tumors, including pancreatic adenocarcinoma, 39 breast and ovarian cancer, 40 synovial sarcoma, 41 head and neck squamous cell carcinoma. 12 High expression of CDK4/CDK6 and/or high expression of CCND1 were also found to be associated with more aggressive behavior and/or poor survival in breast cancer, 42,43 primary ovarian serous carcinomas, 13 papillary carcinoma, 44 meningiomas, 45 periampullary adenocarcinoma, 14 extremity soft-tissue sarcomas, 15 laryngeal squamous cell carcinomas, 46 esophageal adenocarcinoma, 47 and lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 93%
“…Our observations are consistent with other studies, which have found that high expression of phospho-RB1 is associated with an increasing degree of tumor aggressiveness in a variety tumors, including pancreatic adenocarcinoma, 39 breast and ovarian cancer, 40 synovial sarcoma, 41 head and neck squamous cell carcinoma. 12 High expression of CDK4/CDK6 and/or high expression of CCND1 were also found to be associated with more aggressive behavior and/or poor survival in breast cancer, 42,43 primary ovarian serous carcinomas, 13 papillary carcinoma, 44 meningiomas, 45 periampullary adenocarcinoma, 14 extremity soft-tissue sarcomas, 15 laryngeal squamous cell carcinomas, 46 esophageal adenocarcinoma, 47 and lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 93%
“…The L3.6pl pancreatic cancer cell metastatic variant was derived as previously described (19, 20). The selection of L3.6pl GemRes gemcitabine-resistant pancreatic cancer cells was conducted as previously described (12, 21). Cells were maintained in culture with Dulbecco’s Modified Eagle’s Medium/F12 (DMEM/F12) with 10% fetal bovine serum (FBS) (Atlanta Biologicals, Atlanta, GA) and 0.6% penicillin/streptomycin and 5% CO2/95% air at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…L3.6pl metastatic variant was derived as previously described [17, 18]. The selection of L3.6pl GemRes gemcitabine-resistant pancreatic cancer cells was conducted as previously described [19]. All human PC cell lines were authenticated within 6 months by short tandem repeat (STR) analysis.…”
Section: Methodsmentioning
confidence: 99%